Gender, Passage Content and Text Types in Reading Comprehension Among ESL Learners - Fung, Pau Ling (2008)
This study examined the comprehension performance among ESL learners. The aim was to examine whether gender, passage content and text types affect reading comprehension of upper secondary school students in Malaysia. The study also investigated gender differences of students’ reading habits. Their favourite reading topics, reading materials and reading comprehension performances (in terms of passage content and text types) were also explored in relation to gender. The samples comprised 162 Upper Six students. Four reading passages of different contents and text types – female-oriented narrative text, male-oriented narrative text, female-expository narrative text and maleexpository text, were used. They completed reading comprehension tasks (written recall tasks and multiple-choice questions) after reading each of the passages. Both reading comprehension tasks were analyzed to investigate if there were gender differences in reading comprehension performance with respect to passage content and text types. The written recall tasks were also analyzed in order to seek if there were gender differences in terms of quantity of ideas and types of ideas recalled. The respondents were also asked to complete a questionnaire.